2018
DOI: 10.1177/1533317518783278
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Neuropsychiatric Symptoms of Patients With Alzheimer’s Disease

Abstract: The aim of this study was to describe sex differences in neuropsychiatric symptoms (NPSs) in patients with Alzheimer's disease (AD). Baseline scores on the Cohen-Mansfield Agitation Inventory, Neurobehavioral Rating Scale-Agitation subscale, and the Neuropsychiatric Inventory from patients with AD enrolled in a multicenter trial of citalopram for the treatment of agitation were analyzed. We found not only that patients with AD having agitation were likely to exhibit many other NPSs but also that the women in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
5
22
2
Order By: Relevance
“…Our research has found significance in aberrant motor behaviour and delusions, both of which are more frequent in women, which was also defended by Tao et al, (2018), who add that women are more likely to present delusions and hallucinations in vascular dementias or lack of appetite with a diagnosis of major depression, while men with this same diagnosis tended to present greater agitation.…”
Section: Discussion/conclusionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our research has found significance in aberrant motor behaviour and delusions, both of which are more frequent in women, which was also defended by Tao et al, (2018), who add that women are more likely to present delusions and hallucinations in vascular dementias or lack of appetite with a diagnosis of major depression, while men with this same diagnosis tended to present greater agitation.…”
Section: Discussion/conclusionsupporting
confidence: 73%
“…The influence of gender on this variable creates controversy in the literature; our research finds that the percentage of women who present one or more BPSD is higher than that of men. There are data that support this difference, for example, the study by Tao et al (2018) states that 47.6% of women had 2 or more symptoms compared to 39.8% of men. But we have also found studies opposed, such as one conducted by Yatawara, Hiu, Tan and Kandiah (2018) who found that men were at greater risk of presenting this type of disorder.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of antipsychotics did not show differences by gender, our results showed an inequality in antidepressant treatment, since these drugs were prescribed more often for women in all the statistical models. In studying differences in the NPS of male and female patients with Alzheimer’s disease in a clinical sample, Tao et al concluded that women displayed greater heterogeneity in the presentation of NPS, but no significant differences in the number 21. In our study, there were no consistent differences when patients were classified according to their socioeconomic status measured by the deprivation index.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies have reported that females with AD were more likely to exhibit a broader range of NPS than males with AD. 7 , 8 One observational study investigating outpatients with AD observed reclusiveness and emotional lability to be related to the female gender, while apathy and vegetative signs were highly related to the male gender. 9 Moreover, evidence has revealed that women with AD experience significantly greater cognitive impairments across a wide range of cognitive domains, including both visual and verbal processing, as well as semantic and episodic memory.…”
Section: Introductionmentioning
confidence: 99%